Development and characterization of bilayer films of FucoPol and chitosan. (20th August 2016) - Ferreira, Ana R.V.; Torres, Cristiana A.V.; Freitas, Filomena; Sevrin, Chantal; Grandfils, Christian; Reis, Maria A.M.; Alves, Vítor D.; Coelhoso, Isabel M.
Highlights: FucoPol/chitosan bilayer films were prepared for application in food packaging. Bilayer films showed good optical and mechanical properties. Bilayer films are poor barriers to water vapour but excellent barriers to gases. Bilayers presented enhanced properties comparing to FucoPol monolayer films. Abstract: Bilayer films of FucoPol and chitosan were prepared and characterized in terms of optical, morphologic, hygroscopic, mechanical and barrier properties, to evaluate their potential application in food packaging. Bilayer films have shown dense and homogeneous layers, and presented enhanced properties when comparing to monolayer FucoPol films. Though, a high swelling degree in contact with liquid water (263.3%) and a high water vapour permeability (0.75 × 10 −11 mol/ms Pa), typical of polysaccharide films, was still observed. However, they presented a low permeability to O2 and CO2 (0.47 × 10 −16 mol m/m 2 s Pa and 5.8 × 10 −16 mol m/m 2 s Pa, respectively). Tensile tests revealed a flexible and resistant film with an elongation at break of 38% and an elastic modulus of 137 MPa. The studied properties, in particular the excellent barrier to gases, impart these bilayer films potential to be used in packaging of low moisture content products, as well as in multilayered hydrophobic/hydrophilic/hydrophobic barriers for food products with a broader range of water content.